2016
DOI: 10.1007/s00787-016-0846-1
|View full text |Cite
|
Sign up to set email alerts
|

Slow identification of facial happiness in early adolescence predicts onset of depression during 8 years of follow-up

Abstract: Adolescent onset depression places a high burden on those who suffer from it, and is difficult to treat. An improved understanding of mechanisms underlying susceptibility to adolescent depression may be useful in early detection and as target in treatment. Facial emotion identification bias has been suggested as trait marker for depression, but results have been inconclusive. To explore whether facial emotion identification biases may be trait markers for depression, we tested whether the speed with which youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 62 publications
2
13
0
5
Order By: Relevance
“…In the perspective of recent calls for a revision of the categorical DSM system into a more dimensional approach to psychiatry (Kendler, 2012), it may be more beneficial to focus on smaller units of psychopathology, for example symptoms or clusters of symptoms. In support of this, we previously found that facial emotion identification was a stronger predictor of symptoms of anhedonia than of depression itself (Vrijen et al, 2016). Additionally, a potentially viable way to proceed would be to use facial emotion identification biases or deficiencies rather than psychiatric diagnoses or symptoms as the starting point, and from this perspective investigate associations between extreme emotion identification biases or deficiencies and psychiatric symptoms.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the perspective of recent calls for a revision of the categorical DSM system into a more dimensional approach to psychiatry (Kendler, 2012), it may be more beneficial to focus on smaller units of psychopathology, for example symptoms or clusters of symptoms. In support of this, we previously found that facial emotion identification was a stronger predictor of symptoms of anhedonia than of depression itself (Vrijen et al, 2016). Additionally, a potentially viable way to proceed would be to use facial emotion identification biases or deficiencies rather than psychiatric diagnoses or symptoms as the starting point, and from this perspective investigate associations between extreme emotion identification biases or deficiencies and psychiatric symptoms.…”
Section: Discussionsupporting
confidence: 53%
“…All analyses consisted of two steps: first, for each problem domain the effects of the RTs for happy, sad, angry, and fearful emotions were tested separately, adjusted for gender and age (i.e., single-emotion models). Because of tentative evidence that identification patterns across multiple emotions may be more relevant to psychiatric problems than identification of individual emotions (Wright et al, 2009; Oldehinkel et al, 2015; Vrijen et al, 2016), in a second step for each problem domain full emotion models were tested including the RTs for all facial emotions (i.e., multi-emotion models), again adjusted for gender and age. Since the dependent variables (i.e., ASR DSM problem scores) and residuals were not normally distributed, we estimated p -values from 10,000 bootstrap samples to assure the robustness of our results.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, our longitudinal analysis showed that regardless of current depressive symptoms, emotion recognition deficits in youth with DMDD—who mostly had low depressive symptoms at baseline—were predictive of more depressive symptoms at follow‐up. This finding should be interpreted with caution, because levels of attrition were high, but it might suggest that emotion recognition deficits act as a risk factor for depression in youth with DMDD, as such deficits do in healthy youth (Vrijen et al., ). Regardless, our longitudinal findings need replication in a larger sample.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies conducted in people at risk for depression suggest that impaired emotional processing might be an endophenotype of depression (Chan, Norbury, Goodwin, & Harmer, ; Joormann, Talbot, & Gotlib, ; Mannie, Taylor, Harmer, Cowen, & Norbury, ; Monk et al., ). Moreover, these deficits are predictive of depression and depressive symptoms in longitudinal studies (Beevers & Carver, ; Vrijen, Hartman, & Oldehinkel, ). Since irritability is a strong predictor of depression, it is plausible to think that a deficit in emotion recognition in children with severe irritability contributes to increase the risk for depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation